Safety and related factors of treatment with long-term atypical antipsychotic in Chinese patients with schizophrenia: observational study - Lei Zhang; Huafang Li; Yifeng Shen; Wenjuan Yu; Jingjing Huang; Sidi He (General Psychiatry, 2021)
Background Atypical antipsychotics as first-line drugs have been used in patients with schizophrenia in China and abroad. However, its safety still needs to be evaluated in a large population, especially in Chinese patients.Objective The main objective of this study is to evaluate the safety and related factors of long-term atypical antipsychotic use in patients with schizophrenia in China. The secondary objective includes the long-term efficacy of atypical antipsychotics in these patients, as well as pharmacoeconomic evaluation, population pharmacokinetic studies and pharmacogenomics studies.Methods This study has an observational design. The atypical antipsychotics include quetiapine, olanzapine, risperidone, aripiprazole, ziprasidone, paliperidone, amisulpride, perospirone and clozapine. Visits occur at 0, 4, 8, 13, 26, 52, 78, 104, 130 and 156 weeks. The efficacy evaluations include symptoms, social function, recurrence rate and hospitalisation. The safety measures include physical examination, vital signs, abdominal circumference, laboratory tests (such as blood cell analysis, blood biochemical tests and serum prolactin/thyroxine levels), 12-lead ECG, extrapyramidal syndrome assessment, sexual function evaluation, medication and other adverse events. The secondary measures include the Positive and Negative Syndrome Scale, Clinical Global Impression-Severity of Illness Scale, Calgary Depression Scale for Schizophrenia, Personal and Social Performance Scale, relapse rate, drug consolidation, medical-related expenses, income, drug plasma concentration and genetic information.Results This is a large sample, non-interventional and long-term prospective clinical study designed to truly reflect the specific details of clinical practice, fully respect patients’ needs, and understand patients’ treatment intentions and actual treatment details.Conclusions This research method details the aims, methods, study design, strengths and limitations of the study.